Afetividade e cognição no ensino médio: a desconstrução do racionalismo pedagógico - Uller, Waldir (2006)
The present dissertation reports an investigation developed on a Line of Teaching Knowledge Research, introduced to the Masters degree in Education, at Universidade Estadual de Ponta Grossa. The dissertation analyses what passes inside the second grade classroom, from High School, investigating the affectiveness role in the interrelations between student, teacher and, knowledge. It points up the problem which interferes in the students’ learning in the classroom context. By the studies of Piaget’ s works, it defends the unity between emotion and cognition in a learning situation. Questions the situations in which the affectiveness is determinant in the adolescence knowledge construction and, classroom situations result in the student’ s success or failure, inside the learning process. The investigation objectives it raises informations about the interference of emotion in the school everyday, it points up situations of scholarly learnings through an emotionally positive or negative context and diagnosis the scholarly difficulties which are associated with the contexts or the way teachers conduct their classes. It brings as hypotheses that in education and, in learning, the affectiveness is associated with the reason, the emotional state affects in the cognition and the teacher can difficultate or facilitate the learning. It utilizes a methodology with a phenomenological focus and, with an approach of qualitative research. It points up as instruments, the direct observation, interview, questionnaire and, autoscopy. It aims the informations in two temporal blocks: previous and present experiences, in scholarly contexts, and also positive and negative experiences. It plots as categories of analyses: belonging/descentration; praxeology/economy of conduct and value. Presents as result new indagations and, confirms the hypotheses brought, showing that there is a direct relation between affectiveness and cognition. This result is proven by the categories which were utilized